2011
DOI: 10.18294/sc.2011.381
|View full text |Cite
|
Sign up to set email alerts
|

Representaciones sociales relacionadas con la alimentación escolar: el caso de las escuelas públicas de la Ciudad de México

Abstract: Mexico is facing an unprecedented epidemic of obesity and overweight, especially among children. This paper seeks to identify the main social representations related to school meals present in the discourse of different actors within the schools. Twenty interviews with school staff and ten discussion groups with boys and girls from 12 schools were conducted. Three main conceptions were identified in relation to school meals: 1) junk food vs. homemade food; 2) different perspectives on the importance of eating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(53 citation statements)
references
References 20 publications
1
44
0
8
Order By: Relevance
“…Saúde Pública 2018; 34(4):e00142617 se nota em outros contextos escolares com programas de alimentação escolar. Theodore et al 36 , ao estudarem, na Cidade do México, representações sobre a alimentação em escolas beneficiárias de um programa de refeições escolares, identificaram que os escolares, ao mesmo tempo, revelavam um caráter identitário mediante o gosto e o prazer pelas comidas tradicionais como tacos, tortilhas e tamales, como também pelo consumo de alimentos globalizados como a pizza e o refrigerante.…”
Section: Alimentação Escolar E Constituição De Identidades De Sujeição De Resistência E De Identificaçãounclassified
See 1 more Smart Citation
“…Saúde Pública 2018; 34(4):e00142617 se nota em outros contextos escolares com programas de alimentação escolar. Theodore et al 36 , ao estudarem, na Cidade do México, representações sobre a alimentação em escolas beneficiárias de um programa de refeições escolares, identificaram que os escolares, ao mesmo tempo, revelavam um caráter identitário mediante o gosto e o prazer pelas comidas tradicionais como tacos, tortilhas e tamales, como também pelo consumo de alimentos globalizados como a pizza e o refrigerante.…”
Section: Alimentação Escolar E Constituição De Identidades De Sujeição De Resistência E De Identificaçãounclassified
“…Foram selecionadas sete publicações brasileiras 7,8,9,10,11,23,24 , às quais foram agregadas mais nove, identificadas a partir das próprias referências dessas publicações e também de buscas exploratórias, que, embora não mencionassem a temática de identidades, discutiram significados e práticas sobre a alimentação escolar que dialogavam com a constituição de identidades escolares 25,26,27,28,29,30,31,32,33 . A busca também permitiu identificar seis estudos sobre refeições escolares em outros países que permitiram um diálogo com o contexto do PNAE 20,34,35,36,37,38 . Outros estudos sobre identidade 16,18,19,39,40 , PNAE 2,3,41 , práticas alimentares e identidade 13,15 , práticas escolares e identidade 21,22,42,43 , também foram utilizados, assim como documentos e páginas eletrônicas do governo brasileiro.…”
Section: Introductionunclassified
“…Two scenarios are then evident: that of healthy foods represented by fruits and vegetables, but difficult economic access and those unhealthy foods, represented by sugars and sweets, among others, that generate pleasure and are available in the school environment, with prices that can be more accessible than those of fruits and vegetables, which has caused a social representation of healthy eating like inaccessible and difficult to meet. Theodore et al [16] also reported a strong presence in the discourse of the relationship fruits and vegetables with the representation of healthy eating in schoolchildren. Additionally, they identified that food's symbolic classification system could produce a difference between discourse and practice and, too, that around the hierarchy of food mediates as a central function, the eating pleasure.…”
Section: Discussionmentioning
confidence: 97%
“…Some research carried out on social representations of healthy eating in other places has identified a presence in the discourse of the relationship between its consumption and having a good health, pointing to fruits and vegetables as foods that are part of this diet. However, factors such as the price of food, social norms, and the symbolic valuation have also been identified as important factors to explain this difference [4,5,16]. It is so; the research was raised based on the following questions: what does it mean for schoolchildren from an educational institution in Cartagena de Indias, Colombia, their parents, and teachers to have a healthy diet?…”
Section: Introductionmentioning
confidence: 99%
“…En general, los resultados obtenidos acerca del consumo de alimentos coinciden con los recomendados por los programas anteriormente mencionados, los cuales son atribuidos a las estrategias utilizadas: difusión de información nutrimental promocionada mediante el grupo docente en la asignatura de "vida saludable" y durante la activación física, en conjunto con la oferta alimentaria dentro de la escuela, los cuales brindan a las y los niños conocimientos sobre la alimentación. Estos factores también han sido planteados en otros estudios (Olivares, Bustos, Moreno, Lera y Cortez, 2006;Théodore, Bonvecchio, Blanco y Carreto, 2011), en los que además se sugiere que el consumo de ANS tiene una fuerte influencia de la estructuración de las relaciones sociales, en las que circulan saberes y jerarquías sobre los alimentos disponibles en el entorno social inmediato, como el hogar, el barrio o el contexto escolar. Adicionalmente, también se ha evidenciado que la falta de regulación en el expendio de alimentos y bebidas dentro de la escuela influye directamente en el consumo de ANS por parte de las y los niños (Bustos, Kain, Leyton, Olivares y Vio, 2010;Olivares, Yañez y Díaz, 2003).…”
Section: Discussionunclassified